Simulation of wind flow around an alternative flat-roofed fortress tower ruin - Martin Poliak; Michal Franek; Jana Gregorová (Acta Polytechnica)
An analysis of the effects of alternative flat roof sizes and positions on wind flow around a ruin model is presented. The modelled ruin has almost cube-like proportions, with an open roof plane and a destroyed corner. Roofs over ruins are seen as a means of protection against the wind, which is considered a destructive mechanism. The purpose of the roof as a monumental means of presentation and limits of its implementation are also discussed. Wind flow is illustrated by external pressure and skin friction coefficients. Taking their changes into account, the degree of protection flat roof alternatives provide is estimated and optimal flat roof alternatives are discussed. Simulations were carried out using the 3D Time Steady Reynolds-averaged Navier-Stokes equations and the Shear Stress Transport k-ω turbulence model.